2019
DOI: 10.1097/md.0000000000017235
|View full text |Cite
|
Sign up to set email alerts
|

Poststroke depression and risk of recurrent stroke

Abstract: Background:Conflicting results have been reported on the association of poststroke depression with recurrent stroke events. This meta-analysis of prospective studies aims to evaluate whether poststroke depression is an independent predictor of stroke recurrence among stroke patients.Methods:A systematic search of articles in PubMed and Embase databases from their inception to October 2018 was conducted. Prospective studies reporting risk estimates of stroke recurrence by depression status in stroke patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 33 publications
2
46
0
Order By: Relevance
“…A prospective study including patients with concomitant stroke and depression revealed that PSD doubled the risk for stroke recurrence at the end of one year and resulted in a shorter time period for its occurrence [14]. A similar conclusion was drawn in a meta-analysis of six studies performed by Wu et al and further adds that ischemic stroke in particular augmented the risk for re-stroke [15]. On the other hand, the association of PSD is also related to increased risk of death from all causes.…”
Section: Poor Neurological Outcomes In Patients With Post-stroke Deprsupporting
confidence: 54%
See 2 more Smart Citations
“…A prospective study including patients with concomitant stroke and depression revealed that PSD doubled the risk for stroke recurrence at the end of one year and resulted in a shorter time period for its occurrence [14]. A similar conclusion was drawn in a meta-analysis of six studies performed by Wu et al and further adds that ischemic stroke in particular augmented the risk for re-stroke [15]. On the other hand, the association of PSD is also related to increased risk of death from all causes.…”
Section: Poor Neurological Outcomes In Patients With Post-stroke Deprsupporting
confidence: 54%
“…In addition to its negative impact on the quality of life and functional recovery, PSD is also associated with an increased risk of stroke recurrence and mortality [14,15]. A prospective study including patients with concomitant stroke and depression revealed that PSD doubled the risk for stroke recurrence at the end of one year and resulted in a shorter time period for its occurrence [14].…”
Section: Poor Neurological Outcomes In Patients With Post-stroke Deprmentioning
confidence: 99%
See 1 more Smart Citation
“…The Secondary Prevention of Small Subcortical Strokes (SPS3) trial revealed that 19% of stroke patients suffered from post-stroke depression (PSD), while a meta-analysis of 51 observational studies estimates that one out of every three stroke survivors suffer from the PSD [ 9 , 10 ]. Patients with PSD have been shown to have poorer neurological outcomes, and its economic costs are staggering, affecting health systems at a global scale [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 , 2 ] It has a high disability and mortality, which is affected by many risk factors. [ 3 5 ] In the first few hours after AIS, the severity and irreversibility of brain injury increase as time passes. There is often a larger component of brain tissue that is hypoperfused but viable surrounding the irreversible infarction of brain tissue (core infarction), that is penumbra.…”
Section: Introductionmentioning
confidence: 99%